Political imaginaries in the climate movement: Youth-led groups constructing plural views of the future - Silva, D. F. da. (2024)
Since 2018, there has been a notable increase in recognition of the global youth climate movement. Young activists have come into the spotlight through extensive street demonstrations, school occupations, and engagement in other collective actions with the purpose of promoting alternative visions of the future. Multiple scholars have delved into activists’ profiles, their media representations, and other topics. Nevertheless, there is still a lack of research exploring their political imaginaries. This article aims to contribute to understanding how young activists in Portugal assess the current social and political landscape and construct visions of political futures. After analyzing online texts from four climate groups, we identified four themes that offer insights into the political imaginaries of these groups. The four groups discursively negotiate political imaginaries that correspond to a wide spectrum of perspectives, ranging from collective resistance against the neoliberal capitalist system and proposals of decentralized democracy to strategies based on individual ethics and the prevalent discourses of sustainable development and ecological modernization. The plurality of political imaginaries reflects the diversity of sociopolitical stances within youth-led climate movements in Portugal and their commitment to exploring alternative ways of governing climate change.